Crystal Structure and Properties of Imidazo‐Pyridine Ionic Liquids. Issue 18 (26th October 2017) - Farren‐Dai, Marco; Cameron, Stanley; Johnson, Michel B.; Ghandi, Khashayar
Abstract : Computational studies were performed on novel protic ionic liquids imidazolium‐[1, 2‐a]‐pyridine trifluoroacetate [ImPr][TFA] synthesized by the reaction of imidazo‐[1, 2a]‐pyridine (ImPr) with trifluoroacetic acid (TFA), and on fused salt imidazolium‐[1, 2‐a]‐pyridine maleamic carbonate [ImPr][Mal] synthesized by reaction of ImPr with maleamic acid (Mal). Synthesis was performed as one‐pot reactions, which applies green chemistry tenets. Both these compounds begin to decompose at 180°C. Our computational studies suggest another thermal reaction channel, in which [ImPr][Mal] can also thermally polymerizes to polyacrylamide which then cyclizes. This is thermal product remains stable up to 700 degrees, consistent with our thermogravimetric studies. [ImPr][TFA] exhibited good conductivity and ideal ionic behavior, as evaluated by a Walden plot. X‐ray crystallography of [ImPr][TFA] revealed a tightly packed system for the crystals as a result of strong ionic interaction, pi‐stacking, and fluorine—CH interactions. Both synthesized compounds exhibited some CO2 absorptivity, with [ImPr][Mal] outperforming [ImPr][TFA] in this regard. The quantum chemistry based computational methods can shed light on many properties of these ionic liquids, but they are challenged in fully describing their ionic nature. © 2017 Wiley Periodicals, Inc. Abstract : The unique physical and chemical properties of ionic liquids warrant their extensive research in the field of computational chemistry. Here, analysis of the ionic behavior of two novel ionic liquids shows their high conductivity. The syntheses follow green chemistry principles. Crystallography shows the proton transfer between the cation and anion, and the inter‐atomic distances and packing. Carbon dioxide absorptivity is analyzed both experimentally and computationally. Analysis shows ionic liquids to have value in electrolytic applications.